Work-family experience: its relation with self-identity - Aziz, Azelin; Chew Abdullah, Nor Azimah; Ku Ishak, Awanis; Abdul Hamid, Siti Norasyikin (Universiti Teknologi Malaysia, 2016)
Many studies have examined the manner in which demands in work and family roles impact work-family experiences. Given that gender-role somewhat shapes an individual’s self-identity, this study suggests that an individual’s experience of favorable or unfavorable work-family experience depends on his or her self-identity. More specifically, this study aims to investigate whether the compatibility between one’s self-identity and the role in which one is engaged in, results in a buffering effect or a detrimental effect of role demand on the work-family balance experience.